1999
DOI: 10.1097/00005768-199912000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses associated with deer hunting

Abstract: In part, the previously described large HR responses and high rate of cardiovascular complications associated with deer hunting may attributable to the elevated metabolic costs of associated activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…In contrast, the towing condition allowed the participants to remain upright and freely move their arms, allowing for dynamic muscle contractions and subsequent reduced CV responses and perceived relative exertion of the task. Isometric activities such as hunting, snow shoveling, and weight lifting exercises have been associated with increased risk of acute CV events, 2 ,5,8 especially among unfit people. Thus, our findings provide further evidence that if the exercise pressor reflex is present in a healthy population, the ramifications of deer dragging in deconditioned populations with additional CV risk factors may be further contraindicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the towing condition allowed the participants to remain upright and freely move their arms, allowing for dynamic muscle contractions and subsequent reduced CV responses and perceived relative exertion of the task. Isometric activities such as hunting, snow shoveling, and weight lifting exercises have been associated with increased risk of acute CV events, 2 ,5,8 especially among unfit people. Thus, our findings provide further evidence that if the exercise pressor reflex is present in a healthy population, the ramifications of deer dragging in deconditioned populations with additional CV risk factors may be further contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…Haapaniemi et al 2 demonstrated that deer hunting activities result in dramatic increases in heart rate and metabolic responses, leading to increased risk of sudden cardiac death for deconditioned hunters. Likewise, Peterson et al 5 also found dramatic elevations in the CV and hemodynamic responses of deer hunters. To date, alternatives to deer dragging that are less metabolically taxing have not been investigated.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Greater fruit and vegetable consumption, higher nutrient intakes, and lower body weights are associated with fruit and vegetable gardening (Holben et al 2004;Marsh 1998). In contrast, hunting has been associated with increased risk of cardiovascular illnesses (Peterson et al 1999), and concerns exist about exposure to environmental contaminants through consumption of wild fish and game (Burger 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 4 died in the emergency department and 3 while hunting in the field. 6 It is understood that deer hunting involves both strenuous physical activities 3,6,[8][9][10] and psychological stimuli. 11 Haapaniemi et al 8 provided evidence that the high-intensity nature of deer hunting results in dangerous cardiac stresses and suggested fitness may influence a person's relative risk.…”
Section: Introductionmentioning
confidence: 99%